2018
DOI: 10.4208/cicp.oa-2017-0075
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory of Elastic Capsules Under the Effect of Spontaneous Shape

Abstract: Red blood cells can recover their resting shape after having been deformed by shear flow. Their rims are always formed by the same part of the membranes, and the cells are said to have shape memory. Modeled as two-dimensional elastic capsules, their recovery motion and shape memory is studied, mainly focused on the effect of the spontaneous shape. The fluid-structure interaction is modeled using immersed boundary method. Based on the simulations, the resting shapes of capsules are obtained and the area ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…55 and Gou et al. 56 in Figure 3. It is observed that the present results show very good agreement with the previous data.…”
Section: Validationmentioning
confidence: 80%
See 1 more Smart Citation
“…55 and Gou et al. 56 in Figure 3. It is observed that the present results show very good agreement with the previous data.…”
Section: Validationmentioning
confidence: 80%
“…It is noted that a different bending model is used in this problem to be consistent with Sui et al. 55 and Gou et al., 56 but it is sufficient for the purpose of validating the present numerical method.
Figure 2.The schematic diagram for a capsule deformation in a simple shear flow.
…”
Section: Validationmentioning
confidence: 89%
“…Results and validation for Hookean constitutive laws can be found in ref. 176–178. For Skalak models we refer the reader to ref.…”
Section: Benchmarksmentioning
confidence: 99%